Penerapan Etika Jurnalistik pada Konten Berita Program Fakta+62 - Ryan Wahyu Putranto; Ratih Pandu Mustikasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Television make it easier for the audience to understand the message conveyed. This research aims to analyze how the Fact+62 team applies journalistic ethics in news distribution via television, based on the guidelines of the Press Law, Journalism Code of Ethics and P3SPS. This research uses a descriptive qualitative method with an interpretive approach. The focus of this research is the production of news coverage guided by the Press Law, the use of P3SPS as a guide in television news distribution, and the dissemination of news content via Instagram on the @officialnet.news account. However, there are still several aspects that need to be improved, especially regarding the use of images and language that could be considered sensitive or inappropriate. In distributing news content on Instagram, the Fact+62 team does not use the ITE Law as a guideline, but instead follows the implementation of P3SPS in accordance with the direction of the producer responsible for managing the social media account.